Association between toll-like receptor 4 expression and symptoms of major depressive disorder - Wu MK (Dove Medical Press, 2015)
Ming-Kung Wu,1 Tiao-Lai Huang,1,2 Kai-Wei Huang,3 Ya-Ling Huang,1 Yi-Yung Hung1,4 1Department of Psychiatry, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, 2Genomic and Proteomic Core Laboratory, Department of Medical Research, Kaohsiung Chang Gung Memorial Hospital, 3Department of Nursing, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, 4Graduate Institute of Clinical Medical Sciences, Chang Gung University, College of Medicine, Kaohsiung, Taiwan Background: In our previous study, toll-like receptor 4 (TLR4) mRNA expression level was associated with severity of major depressive disorder (MDD) evaluated with the 17-item Hamilton Depression Rating Scale (HAMD-17). However, there are few studies that have investigated the relationship between symptoms of MDD and changes in TLR4 expression. Therefore, the aim of the present study was to further analyze the association between subscales of HAMD-17 and TLR4. Methods: Fifty-one patients with MDD (15 male and 36 female) participated in this study. HAMD-17 was used to assess the symptoms of major depression. The mRNA expression levels of TLR4 were examined in parallel with a housekeeping gene, using real-time polymerase chain reaction. A stepwise linear regression forward model was used to evaluate the relationships between items of HAMD-17 and TLR4 expression. Results: Some sickness behavior-associated symptoms, including suicide, somatic symptoms of anxiety, or performance of work and activities, were not associated with TLR4 expression. However, psychological signs of anxiety and loss of weight in HAMD-17 can predict the expression level of TLR4. Conclusion: Our results suggest a significant association between anxiety, body weight loss, and TLR4 mRNA levels in patients with MDD. Larger longitudinal studies combining both subjective and objective measures of depression are needed to clarify the link between TLR4 and symptoms of depression. Keywords: major depressive disorder, innate immune, toll-like receptor, anxiety